Research on traction motor heat dissipation of high-power permanent magnet direct drive electric locomotive - SONG Andong; ZHANG Jiafeng; GAO Shenglan (机车电传动)
The design of the direct drive transmission structure and the motor air path structure of the traction motor of the high-power permanent magnet direct drive electric locomotive was introduced. The heat dissipation simulation and temperature rise test verification of the permanent magnet motor were compared and analyzed. The temperature rise test of the motor with or without a coupling which proved that the coupling transmission structure had a positive improvement in the heat dissipation of the motor. Focusing on the research and experimental verification of the problem of the bearing high temperature rise in the test, and carrying out the motor temperature rise test under different rotational speeds and different conditions with or without a coupling, the relationship between temperature rise of motor bearing and heating of rotor permanent magnet was provided and analyzed. The magnetic steel segmented technology of rotor permanent magnet was used to reduce the magnetic loss of rotor. Through theoretical analysis and test, it was proved that the bearing temperature rise of magnetic steel segmented motor is significantly lower than that of non-magnetic steel segmented motor. Through the research on the heat dissipation technology of the permanent magnet direct drive motor, it was proved that the use of the magnetic steel segment technology for the motor rotor of the high-power permanent magnet direct drive electric locomotive can effectively reduce the motor loss, and the use of the direct drive motor to connect the coupling transmission structure further reduces the temperature rise of the motor. It lays a foundation for the subsequent high-power permanent magnet direct drive motor heat dissipation design and reliable application of high-power permanent magnet direct drive technology in the rail transit industry, and provides useful design experience.